Economic analysis of rehabilitation approaches for water distribution networks: comparative study between Egypt and Malaysia - Abdelrahman, M. Farouk; Rahimi, A. Rahman; Noor Suraya, Romali (Emerald Publishing Limited, 2021)
Purpose – Sustainable water management has been a trending goal in the past decade. Non-revenue water (NRW) is one form of water loss that should be addressed to reach water sustainability. While rehabilitating water distribution networks (WDNs) is one way to decrease NRW, the process is often delayed owing to cost. Therefore, it is essential to provide decision-makers with cost-effective approaches to optimize WDN rehabilitation. This study aims to evaluate the cost-effectiveness of approaches for rehabilitating WDN from developing countries’ perspectives.